The impact of trauma-awareness session on police officers’ trauma-informed attitudes in Scotland - Brodie, Zara P. (Psychology, crime & law, 2025)
Following reports that up to 80% of calls received by police in Scotland concern vulnerability issues, adoption of trauma-informed policing has taken priority. This is the first evaluation of the impact of a brief trauma-awareness training session on police officers’ trauma-informed attitudes. Participants from two Scottish police divisions - one who had been exposed to trauma-awareness training (n = 62) and one who had not (n = 91) - completed self-report questionnaires on their trauma-informed attitudes. Officers displayed more positive trauma-informed attitudes towards victims/witnesses than suspects/perpetrators (p < .001). Female officers (p = .002), those with longer service (p = .018) and marginally those who were older (p = .048) demonstrated more trauma-informed attitudes; officer rank was unrelated. Female officers who received the training had significantly higher trauma-informed attitudes towards both groups than male officers who received the training (p < .001), and higher trauma-informed attitudes towards suspects/perpetrators than both male and female officers who had not - though marginal (p = .048). Findings indicate that the Resilience trauma-awareness has limited potential to influence trauma-informed attitudes, which appear to be more dependent upon officer age, gender and experience. However, female officers may be more susceptible to awareness training than male officers. To meaningfully increase trauma-informed attitudes, a more intensive tool-based training programme may be required.